THE ROLE OF ARTIFICIAL INTELLIGENCE IN IMPROVING THE EDUCATIONAL PROCESS (International journal of artificial intelligence, 2026)
Artificial Intelligence (AI) has rapidly become one of the most transformative technologies of the 21st century, significantly influencing various sectors, including education. The integration of AI into the educational process offers new opportunities to enhance teaching quality, personalize learning, improve assessment methods, and optimize educational management. This article explores the role of artificial intelligence in improving the educational process using the IMRAD structure (Introduction, Methods, Results, and Discussion). The study analyzes existing literature, practical applications, and case examples of AI-based educational tools. The results demonstrate that AI contributes to increased learning efficiency, learner engagement, and teacher support, while also presenting challenges such as ethical concerns, data privacy, and unequal access. The article concludes that AI, when applied responsibly, can play a crucial role in building a more effective, inclusive, and adaptive educational system.